Perancangan dan Implementasi Sistem Penjurian Panahan Berbasis Web Dengan Fitur Pemantauan Statistik Real-time - Gilang Ramadhan; Budi Hartono; Arsito Ari Kuncoro (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2026)
The judging process in archery plays an important role in determining the results of a competition in a fair, accurate, and transparent manner. However, in practice, the judging process at the club level is still largely done manually, which can potentially cause delays in score recapitulation, recording errors, and a lack of transparency in the results of the competition. This study aims to design and implement a web-based archery judging system with real-time archer statistics monitoring features using the Rule-Based Logic method. The research method used is research and development (R&D) with the Waterfall Software Development Life Cycle (SDLC) model, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using web technology with a client-server architecture and implements archery scoring rules in the form of IF-THEN logic to ensure consistency and accuracy in score calculations. Test results show that the system is able to significantly speed up the score recapitulation process compared to manual methods, as well as display judging results and archer statistics in real-time in the form of tables and graphs. The application of Rule-Based Logic has also proven effective in reducing potential scoring errors and increasing the objectivity of competition results. Thus, the developed system is capable of improving the efficiency, accuracy, and transparency of the archery judging process, and has the potential to become a digital solution that can be applied to archery judging activities at a broader level.